The Use of Multi Sources Data for Mapping of Sensitive Areas to Hydrous Erosion in the Mountains of Tessala (Northern Algeria) - Bouiadjra, Salah Eddine Bachir; El Zerey, Wael (International Journal of Environment, 2014)
The Tessala mountains constitute a fragile ecosystem, they are confronted with several problems with knowing loss of the farmed lands, bad distribution and occupation of the soil, low organic matter, rough and unstable soil (the slope exceeds in some places the 25%). To understand the problem of hydrous erosion in the Tessala mountains, a model of approach using geographic information system was proposed. Geographic data were processed by mapping using specialized software. After treatment, we identified the areas where the susceptibility to erosion is significant. Over 80% of the land of our study area is susceptible to hydrous erosion at different degrees highly sensitive (32.5%), moderately sensitive (44%) insensitive (15%) and stability (7.5%). DOI: http://dx.doi.org/10.3126/ije.v3i3.11092 International Journal of Environment Vol.3(3) 2014: 321-331